ANALISIS FAKTOR RISIKO GANGGUAN MUSKULOSKELETAL PADA PEKERJA SHIFT PAGI ASSEMBLING 1 DI PT. X SUNTER ASSEMBLY PLANT JAKARTA UTARA - Fadilla Nela Chairana; Suroto Suroto; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2017)
Musculoskeletal Disorders is a disorder of the muscles, tendons, and nerves caused by repetitive motion, fast, heavy workload, awkward posture, vibration and low temperatures. Based on the preliminary results of a survey that was carried out against two team member line chassis Assembling 1 complained of neck and back pain during and after work, and the prevalence of the disease in September 2014 mentions the existence of pain around the head (75.4%), neck pain (37.9 %), lower back pain (18.9%) and strains (15%). This research aims to analyze the risk factors for musculoskeletal disorders in shift workers Assembling 1 PT. X Sunter Assembly Plant. This research is a descriptive qualitative with in-depth interviews and mapping nordic body map. Subjects of this research amounts to 5 people as the main informant and 2 as informant triangulation. The results showed that the risk factors that most affecting is the awkward posture in certain parts of the body inculuding wrist, arm, neck, shoulder, back, waist and legs with repetitive motion. The risk factor of workload is still appropriate 5-7 kg using hydraulic tools. Researchers also suggest that stretching corresponding to the location of the working man power.